2022
DOI: 10.3390/pr10030571
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Self-Learning Artificial Bee Colony Optimization Algorithm for Flexible Job-Shop Scheduling Problem with Job Insertion

Abstract: To solve the problem of inserting new job into flexible job-shops, this paper proposes a dynamic self-learning artificial bee colony (DSLABC) optimization algorithm to solve dynamic flexible job-shop scheduling problem (DFJSP). Through the reasonable arrangement of the processing sequence of the jobs and the corresponding relationship between the operations and the machines, the makespan can be shortened, the economic benefit of the job-shop and the utilization rate of the processing machine can be improved. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…To verify the effectiveness of the proposed QL-AO, it is compared with the most classic algorithms, GA and PSO, three novel algorithms, ABC, CS and JAYA, and the basic AO. In addition, Q-learning-based genetic algorithm (QL-GA) and Q-learning-based artificial bee colony algorithm (QL-ABC), proposed by Chen et al [35] in 2020 and Long et al [36] in 2022, respectively, are selected as comparison algorithms. In fairness, the competitive algorithms used the same heuristic initialization method as QL-AO.…”
Section: Algorithm Comparisonmentioning
confidence: 99%
“…To verify the effectiveness of the proposed QL-AO, it is compared with the most classic algorithms, GA and PSO, three novel algorithms, ABC, CS and JAYA, and the basic AO. In addition, Q-learning-based genetic algorithm (QL-GA) and Q-learning-based artificial bee colony algorithm (QL-ABC), proposed by Chen et al [35] in 2020 and Long et al [36] in 2022, respectively, are selected as comparison algorithms. In fairness, the competitive algorithms used the same heuristic initialization method as QL-AO.…”
Section: Algorithm Comparisonmentioning
confidence: 99%
“…The parameters of the original ABC algorithm are the number of food sources (SN), which is equal to the number of employed or spectator bees [4], [17], the number of attempts after which a food source must be abandoned (limit), and the criterion of termination. The main phases of the original algorithm as shown in Figure 2.…”
Section: Artificial Bee Colony (Abc)mentioning
confidence: 99%
“…More and more scholars have found that meta-heuristic algorithms, due to their simplicity, efficiency, and wide applicability, show significant advantages in solving combinatorial optimization problems such as the MTSP [17][18] and the JSP [19][20], which provide the feasibility and effectiveness of the efficient solution of such complex problems. In terms of algorithm design, scholars have proposed hybrid meta-heuristic algorithms combining techniques such as the dragonfly algorithm (DA), firefly algorithm (FA), and genetic algorithm (GA) [21][22].…”
Section: Introductionmentioning
confidence: 99%